TINJAUAN YURIDIS TERHADAP PENANGANAN KECURANGAN DALAM PILKADA 2020 OLEH BAWASLU KABUPATEN NUNUKAN - Anggraini, Inah; Rahmat, Diding (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2025)
The implementation of the 2020 Regional Head Election (Pilkada) in Nunukan Regency presents its own challenges, especially related to the potential for fraud that can damage the integrity of the democratic process. This study aims to legally examine the forms of fraud that occurred and how the handling was carried out by the General Election Supervisory Body (Bawaslu) of Nunukan Regency based on the latest regulations. The method used is normative legal with a statutory and case approach, and is strengthened by empirical data through interviews and documentation. Based on the results of the study, Bawaslu has carried out its supervisory and violation handling functions in accordance with the provisions of Law Number 10 of 2016 and Bawaslu Regulation Number 9 of 2024 concerning amendments to Bawaslu Regulation Number 8 of 2020. The process of handling alleged fraud is carried out through the stages of receiving reports, initial studies, clarification, to providing recommendations for administrative sanctions or delegation to law enforcement through the Gakkumdu Center. The effectiveness of the implementation can be seen from the response to public reports and findings of violations, especially related to money politics and violations of health protocols. However, implementation in the field still faces various obstacles such as limited human resources, difficult geographical access in border areas, low legal literacy of voters, and less than optimal collaboration between election organizing institutions. This study concludes that although normatively Bawaslu has a strong legal basis, in practice it still needs to strengthen institutional capacity and increase community participation in order to create more effective and comprehensive election supervision, especially in areas with social and geographical complexity such as Nunukan Regency.